Cellular and Cytokine Responses in Lymph Node Granulomas of Bacillus Calmette Guérin (BCG)-Vaccinated and Non-vaccinated Cross-Breed Calves Naturally Infected With Mycobacterium bovis - Sirak, Asegedech; Tulu, Begna; Bayissa, Berecha; Gumi, Balako; Berg, Stefan; Salguero, Francisco J.; Ameni, Gobena; , The ETHICOBOTS Consortium (Frontiers in Veterinary Science, 2021)
Local immunological responses at the site of infections, such as at the lymph nodes and lungs, do play a role in containing infection caused by Mycobacterium bovis (M. bovis). This bovine tuberculosis (bTB) study was conducted to evaluate cellular and cytokine responses in the lymph nodes and lungs of BCG-vaccinated and non-vaccinated calves that were naturally infected with M. bovis. Immunohistochemical assays were used for examination of the responses of macrophages, T cells, cytokines and chemical mediators of 40 (22 vaccinated and 18 non-vaccinated) Holstein-Friesian-zebu crossbred calves that were naturally exposed for one year to a known bTB positive cattle herd. The incidence rates of bTB visible lesion were 68.2% (15/22) and 89% (16/18) in vaccinated and non-vaccinated calves, respectively. The local responses of CD4+ and CD8+ T cells, and those of IFN- and TNF-α within the lesions, were stronger (P<0.05) in BCG-vaccinated calves than in non-vaccinated calves. However, there was no statistically significant difference between the two groups (P>0.05) in the response of CD68+ cells. Thus, the findings of this study indicated stronger responses of a set of immunological cells and markers at the local granulomas of BCG-vaccinated calves than in non-vaccinated calves. Furthermore, BCG vaccination may also play a role in reducing the severity of the gross pathology at the primary site of infection.